The Role Of Environmental Law In Preventing Environmental Damage And Pollution (Case Study Of Mount Sirnalanggeng Mining In Karawang) - Dede Rohmat; Sadino Sadino (JURNAL HUKUM SEHASEN, 2024)
The environment cannot be separated from humans, which is a vital context that is closely related to human life. It can have positive impacts if it is well cared for, but can also have detrimental impacats if it is contaminated or polluted without adequate supervision. Mount Sirnalanggeng, which is located in Tegalwaru sub-district, Karawang district, has now changed its shape and biological system due to mining carried out by PT Atlasindo Utama. The spring has disappeared, the water channels in the Cipadagungan and Cicaban rivers dry up during the dry season, the West Tarum irrigation system has been affected, resulting in the water supply to DKI Jakarta decreasing by 4,500 liters every second. The purpose of writing this research is to find out the role of environmental law in preventing environmental damage and pollution, specifically in the case study of Mount Sirnalanggeng Karawang mining. The method used in this research is the Normative-Empirical method with a statutory approach and case studies, data collection techniques namely interviews and literature studies. Based on the research results, the mining carried out by PT. Atlasindo Utama has complied with Law No. 32 of 2009 concerning Environmental Protection and Management, Law Number 3 of 2020 concerning Mineral and Coal Mining and Karawang Regency Regional Regulation No.14 concerning Environmental Protection and Management. The company also committed 3 (three) criminal acts, namely providing false reports, carrying out illegal mining, and not carrying out post-mining reclamation.